Green Finance, Environment Performance, and CSR on Financial Performance Industrial Sector in Indonesia: The Moderating Role of Good Corporate Governance - Asyifa, Ninette I.; Endri, Endri (International Journal of Applied Management and Business, 2025)
This study aims to analyze the influence of Green Finance, Environmental Performance, and Corporate Social Responsibility (CSR) on financial performance, with Good Corporate Governance (GCG) as a moderating variable, in industrial sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The research sample consists of 41 companies, employing panel data regression analysis processed using E-Views 13. The findings reveal that Green Finance, Environmental Performance, and CSR have a significant effect on Return on Assets (ROA), and that GCG is proven to moderate these relationships. Meanwhile, only Green Finance and GCG significantly affect Return on Equity (ROE), with GCG moderating solely the effect of Green Finance on ROE. These results underscore that the effective implementation of GCG can strengthen the impact of corporate sustainability practices on financial performance and support long-term business continuity.